Peran Self-Efficacy terhadap Penyesuaian Diri pada Mahasiswa Tahun Pertama di Universitas Setia Budi - Wibisono, Dea Banowati; Dwi Nugroho, Yustinus Joko; Sujoko (Journal of Psychosociopreneur, 2024)
The purpose of this study is to ascertain how self-efficacy affects adjustment in first-year Setia Budi University students.. 260 students were the sample utilized in this study, which employed basic random sampling methods. Quantitative approaches are employed in this study. The self-adjustment and self-efficacy scales are the measuring tools used in this study. Using SPSS 22.0 for Windows, a basic regression analysis technique is employed for data analysis. The data analysis results indicate a significant involvement of the self-efficacy variable in self-adjustment, with a significance value of 0.000 (p < 0.05). Additionally, the study's findings indicate a R Square value of 0.255, indicating a positive role of 25.5%. Based on this, it can be deduced that the self-efficacy variable has a positive effect, with higher levels of self-efficacy translating into higher levels of self-adjustment. The study's premise, according to a straightforward regression analysis test, is accepted: self-efficacy plays a part in self-adjustment